2019
DOI: 10.1177/0020764019866230
|View full text |Cite
|
Sign up to set email alerts
|

Perception of social support and psychotic symptoms among persons with schizophrenia: A strategy to lessen caregiver burden

Abstract: Background: Improving patients’ perception of social support is significant not only for their re-adaptation to life but also for alleviating caregivers’ burden. Aim: This study aims to examine an integrated model regarding social support, psychotic symptoms and caregiver burden. Methods: Persons with schizophrenia ( N1 = 300) and their family caregivers ( N2 = 300) in Xinjin County, Chengdu, China, completed the survey to report their demographics, patients’ perception of social support (Duke Social Support I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 61 publications
8
28
0
2
Order By: Relevance
“…It is common as the caregiving responsibilities are often delegated to family members with the least economic value [20]. Available services, resources, and support for patients and their family caregivers could help to relieve the burdens on caregivers [21]. The awareness and utilization of disability certificates ranked the first in our study.…”
Section: Discussionmentioning
confidence: 82%
“…It is common as the caregiving responsibilities are often delegated to family members with the least economic value [20]. Available services, resources, and support for patients and their family caregivers could help to relieve the burdens on caregivers [21]. The awareness and utilization of disability certificates ranked the first in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Available services, resources, and support for patients and their family caregivers could help to relieve the burdens on caregivers [21]. The awareness and utilization of disability certi cates ranked the rst in our study.…”
Section: Discussionmentioning
confidence: 83%
“…It has also been shown that schizophrenia patients receive less social support compared to healthy controls (39,40). Studies report increased subjective social support shows correlation with a lower degree of psychotic symptoms (7), and emotional and socialization supports are helpful for schizophrenia patients (9). On the contrary, exposure to social stress is strongly associated with onset of psychosis, schizophrenia in particular (41).…”
Section: Discussionmentioning
confidence: 99%
“…Social support can help individuals to cope with everyday life, particularly in response to critical situations. Increased subjective social support shows correlation with a lower degree of psychotic symptoms (7,8). Social support can provide a buffer against psychosocial stressors and protect against the negative effects of SLE in schizophrenia (7,9).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation